The Botanical Drug PBI-05204, a Supercritical CO2 Extract of Nerium Oleander, Inhibits Growth of Human Glioblastoma, Reduces Akt/mTOR Activities, and Modulates GSC Cell-Renewal Properties - Colapietro, Alessandro; Yang, Peiying; Rossetti, Alessandra; Mancini, Andrea; Vitale, Flora; Martellucci, Stefano; Conway, Tara L.; Chakraborty, Sharmistha; Marampon, Francesco; Mattei, Vincenzo; Gravina, Giovanni Luca; Biordi, Assunta Leda; et al. (Frontiers in Pharmacology, 2020)
Glioblastoma Multiforme (GBM) is the most common glial brain tumor resulting in very low patient survival despite current extensive therapeutic efforts. Emerging evidence suggests that more effective treatments are required to overcome tumor heterogeneity, drug resistance and a complex tumor-supporting microenvironment. PBI-05204 is a specifically formulated botanical drug consisting of a modified supercritical C02 extract of Nerium oleander that has undergone both Phase I and Phase II clinical trials in the United States for treatment of patients with a variety of advanced cancers. The present study aimed to investigate the antitumor efficacy of this botanical drug against glioblastoma using both in vitro and in vivo cancer models as well as exploring efficacy against glioblastoma stem cells. All three human GBM cell lines, U87MG, U251, and T98G, were inhibited by PBI-05204 in a concentration dependent manner that was characterized by induction of apoptosis as evidenced by increased ANNEXIN V staining and caspase activities. The expression of proteins associated with both Akt and mTOR pathway was suppressed by PBI-05240 in all treated human GBM cells tested. PBI-05204 significantly suppressed U87 spheroid formation and the expression of important stem cell markers such as SOX2, CD44, and CXCR4. Oral administration of PBI-05204 resulted in a dose-dependent inhibition of U87MG, U251 and T98G xenograft growth. Additionally, PBI-05204 treated mice carrying U87-Luc cells as an orthotropic model exhibited significantly delayed onset of tumor proliferation and significantly increased overall survival. Immunohistochemical staining of xenograft derived tumor sections revealed dose-dependent declines in expression of Ki67 and CD31 positive stained cells but increased TUNEL staining. PBI-05204 represents a novel therapeutic botanical drug approach for treatment of glioblastoma as demonstrated by significant responses with in vivo tumor models. Both in vitro cell culture and immunohistochemical studies of tumor tissue suggest drug induction of tumor cell apoptosis and inhibition of PI3k/mTOR pathways as well as cancer stemness. Given the fact that PBI-05204 has already been examined in Phase I and II clinical trials for cancer patients, its efficacy when combined with standard of care chemotherapy and radiotherapy should be explored in future clinical trials of this difficult to treat brain cancer.